State of proteolytic and fibrinolytic processes in the brain of rats with experimental diabetes mellitus complicated by cerebrovascular accident in the basin of the carotid arteries - Tkachuk, S.; Tkachuk, O.; Povar, M.; Yasinska, O.; Denysenko, O. (Journal of Education, Health and Sport, 2021)
Introduction. The imbalance in the protease-antiprotease system is an integral part of the pathogenesis of acute disorder of cerebrovascular circulation and diabetes mellitus (DM), but its manifestations in the complication of diabetes by ischemia-reperfusion of the brain have not been investigated yet. The objective of the work – to study the dynamics of carotid ischemia-reperfusion effect on the proteo- and fibrinolytic activity in brain structures of rats with experimental DM. Rats with the four-month streptozotocin DM were modeled bilateral carotene ischemia during 20 minutes. In homogenates of brain structures, indicators of proteo- fibrinolytic activity were determined after 1 hour from the beginning of reperfusion and during the 12th day of the post-ischemic period. In the absence of DM, the proteolytic activity of all or individual indicators il increased in both periods of the post-ischemic period in the cortex of the frontal and occipital lobes, the fields of hippocampus CA2 and CA3, and during the 12th day in the field CA1. Results. In rats with diabetes, in all brain structures, there are no changes in the lysis of azo-albumin and azo-casein in both terms of observation and lysis of collagen progressively decreases. In rats without DM in the cortex of the studied particles, fields of the hippocampus CA1 and CA2, all or separate indices of fibrinolytic activity are increased in both periods of the post-ischemic period, in the field CA3 – all indices at the 12th day. In the presence of diabetes in the cortex of both studied lobes and the field CA1, the fibrinolytic activity decreases in the late post-ischemic period, in the fields of CA2 and CA3 – during both observation periods. Conclusion. In the brain structures under investigation at both time intervals, the DM eliminates the reaction of low and high molecular weight proteins to the ischemia-reperfusion and suppresses fibrinolytic activity.